The Effect Of Brand Identification And Self-Concept Connection On Brand Love And Its Implications For Brand Loyalty - Devi Dwi Agusthera; Theresia Militina; Saida Zainurrosalmia ZA (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
This study aims to analyze and find out Brand Identification, Self-Concept Connection, Brand Love and Brand Loyalty for iPhone brand Smartphone users in Samarinda. The background of this research refers to the relationship between Brand Identification and Self-Concept Connection that is woven by the iPhone Brand with its users. Besides seeing how the Brand Identification and Self-Concept Connection formed the Brand Love and Brand Loyalty iPhone smartphone users in Samarinda. Brand Identification and Self-Concept Connection may not necessarily create optimal love for iPhone smartphone users in Samarinda, so it needs to be reevaluated along with how much influence it has on brand loyalty. This research is a quantitative descriptive study and uses SEM-AMOS v.22, analysis tool with the SAMPLE formula = Σ Indicator x (5-10), which then selected samples of 102 respondents. Data collection techniques using the proportional accidental sampling method. The results showed that five proposed hypotheses were accepted namely Brand Identification had a significant effect on Brand Love, Self-Concept Connection had a significant effect on Brand Love, Brand Identification had a significant effect on Brand Loyalty, Self-Concept Connection had a significant effect on Brand Loyalty and Brand Love had a significant effect towards Brand Loyalty. These findings support the theory and previous research that became the reference of researchers.